Architectural Regionality in the Formation of Regional Identity in Medan City - Eddy, Firman; Abdillah, Wahyu; Novrial (Talenta Publisher, 2025)
The development of the times and socio-cultural changes have had a significant impact on architecture, often eroding regional identity and cultural heritage that have been formed over centuries. This is evident in the revitalization of heritage areas, where regional design elements are less integrated, especially in contemporary practices. This study proposes a policy to implement regional architectural design and organize outdoor spaces in cultural heritage revitalization projects. Using architectural design methods, this study aims to create a